Immunosuppressive tumor microenvironment and advance in immunotherapy in melanoma bone metastasis - Ma, Yiqun; Zhang, Lin; Liu, Weimin (Frontiers in Immunology, 2025)
Melanoma frequently develops bone metastases, leading to skeletal-related events and poor survival. The tumor microenvironment (TME) plays a pivotal role in melanoma progression, bone metastasis, and immunotherapy resistance. Key immunosuppressive cells including myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs), regulatory T cells (Tregs), and cancer-associated fibroblasts (CAFs) promote immune evasion and osteolytic bone destruction via RANKL-dependent and -independent mechanisms. Immune checkpoint inhibitors (ICIs), including anti-CTLA-4 and anti-PD-1/PD-L1 therapies, have revolutionized melanoma treatment, yet resistance remains common due to TME immunosuppression. Emerging strategies, such as combination therapies, aim to enhance efficacy by reshaping the TME. This review synthesizes current knowledge on TME-driven immunosuppression, bone metastasis mechanisms, and immunotherapeutic advancements, offering insights into overcoming resistance and improving patient outcomes.